(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
أظهرت نتائج دراسة شدة الإصابة بمرض الجرب على التفاح في موقع الدراسة /قرية الخضراء/ منطقة الباير في الموسمين الزراعيين 2000/2001 و2001/2002 تبايناً واضحاً، ففي حين انخفضت شدة الإصابة في الموسم الأول كانت في أوجها في الموسم الثاني حيث سادت الظروف الجوية الملائمة لانتشار وتطور المرض. بلغت شدة الإصابة في الموسم 2001/2002 حوالي 81.01% للصنف غولدن ديليشيس و83.4% للصنف ستاركنغ ديليشيس. في حين لم تتجاوز 25% للصنف غولدن و27.3% للصنف ستاركنغ للموسم 2000/2001، وهذا انعكس سلباً على كميات التفاح المنتجة في الموسمين 2000/2001 و2001/2002. في المخزن ونتيجة متابعة الإصابة على الثمار لوحظ أنه لم تتطور عند تخزينها لمدة خمسة أشهر في كلا الموسمين إلا أنها كانت أكثر عرضة للإصابة بالأمراض التخزينية الأخرى. إن إصابة ثمار التفاح بمرض الجرب قللت من قيمتها الاقتصادية وأدت إلى خفض بعض مكوناتها مثل السكريات وفيتامين C والمواد الصلبة الذائبة بينما أدت إلى زيادة كمية الأحماض العضوية في الثمار وذلك بمقارنتها مع الثمار السليمة. وزادت كمية الماء المفقودة من الثمار بسبب تهديم طبقة الكيوتيكل التي تحمي الثمرة. The results of studding the effects of infection of (Apple scab) on components of Apple fruit in Al-Khadraa of the Bayer district during 2 seasons (2000/2001 ; 2001/2002) shwoed a serious difference. The infection was low in the first season (2000/2001), but, very high in the next season (2001/2002), because the climate factors were very suitable to the desease to spread and develop. The effect of infection in the 2 season (2000/2001 ; 2001/2002) was: 25% for Golden delicious, 27% for starking delicious and 81.01% for Golden delicious, 83.4% for starking delicious respectively. This result negatively affects the production of apple fruit in both seasons (2000/2001; 2001/2002). In the store the infection of the fruit did not develop after storing for 5 months in both seasons, but it was susceptible to other store diseases. Infection of Apple scab on Apple fruit decreases the economical value and some of apple components reducing its sugar, vitamin C, and soluble solids, but it increases the organic acids (Malic acid) of infected fruits compared to uninfected ones. It also increases the transpiration of the fruit, because it destroys the cuticle derm protecting it.